2020
DOI: 10.3389/fendo.2020.00393
|View full text |Cite
|
Sign up to set email alerts
|

PLS3 Mutations Cause Severe Age and Sex-Related Spinal Pathology

Abstract: Objective: Mutations in the X-chromosomal PLS3-gene, encoding Plastin 3, lead to severe early-onset osteoporosis, suggesting a major role for PLS3 in bone metabolism. However, the consequences of abnormal PLS3 function in bone and other tissues remain incompletely characterized. This study evaluated spinal consequences of aberrant PLS3 function in patients with PLS3 mutations. Design: A cross-sectional cohort study with spinal magnetic resonance imaging of 15 PLS3 mutation-positive (age range 9-77 years) and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Pls3 KO mice demonstrated an osteoporotic phenotype, while PLS3 overexpressing mice showed hyperostosis [ 26 ]. PLS3 was detected in the dendrites of osteocytes [ 59 ], and it has been suggested that PLS3 might be involved in the mechanotransduction [ 18 , 27 , 28 , 60 ] and seems also to be involved in osteoclastogenesis [ 26 ]. Interestingly, we found that PLS3 was mainly located at the upper zone of the OA cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pls3 KO mice demonstrated an osteoporotic phenotype, while PLS3 overexpressing mice showed hyperostosis [ 26 ]. PLS3 was detected in the dendrites of osteocytes [ 59 ], and it has been suggested that PLS3 might be involved in the mechanotransduction [ 18 , 27 , 28 , 60 ] and seems also to be involved in osteoclastogenesis [ 26 ]. Interestingly, we found that PLS3 was mainly located at the upper zone of the OA cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…There are only very few studies analyzing the role of PLS3 in cartilage. Mäkitie et al [ 28 ] investigated spinal changes in patients with PLS3 mutations. Although the spinal structures demonstrated severe and progressive alterations in, e.g., vertebra height and shape, pathologies at the intervertebral discs were not present.…”
Section: Introductionmentioning
confidence: 99%
“…To analyze the proposed functions of PLS3 regarding mechanotransduction [5,15,108,120,143,144,148], Ca 2+ regulation [23,33,149], osteoblastic bone mineralization [15,120,126,131,134,143,144,150], osteoclastogenesis [16] and vesicular trafficking [15,16,61,151], various PLS3 mutations have been investigated and mouse model studies established to specifically investigate the effect of PLS3 loss or overexpression [16].…”
Section: Osteoporosismentioning
confidence: 99%
“…So far, less is known about the effect of PLS3 deletions on cartilage. Another study has shown no effect on the intervertebral disc of osteoporosis patients linked to loss of function and PLS3 deletions [148]. The influence of PLS3 overexpression, PLS3 loss, and PLS3 mutations on articular cartilage itself remains elusive and the underlying mechanism affecting cartilage health still needs to be explored.…”
Section: Osteoarthritismentioning
confidence: 99%
“…Furthermore, it is difficult to “quality control” the data that is interrogated. For example, there are several papers that assign different activities to PLS3 but no clear function for the protein has yet emerged and it is still unclear whether its major role is in osteoblasts or osteoclasts or both ( 85 ).…”
Section: Obstacles and Opportunitiesmentioning
confidence: 99%